The Effect of Curcumin on Idiopathic Parkinson Disease: A Clinical and Skin Biopsy Study. Issue 7 (13th May 2022) - Donadio, Vincenzo; Incensi, Alex; Rizzo, Giovanni; Fileccia, Enrico; Ventruto, Francesco; Riva, Antonella; Tiso, Domenico; Recchia, Martino; Vacchiano, Veria; Infante, Rossella; Petrangolini, Giovanna; Allegrini, Pietro; et al.
Abstract: There are currently no standardized therapies for Parkinson disease (PD). Curcumin shows anti-amyloidogenic properties in vitro and may be a promising treatment for PD. We evaluated the effects of curcumin supplementation on clinical scales and misfolded, phosphorylated α-synuclein (p-syn) accumulation in skin biopsies in 19 PD patients who received curcumin supplementation for 12 months and 14 PD patients to treated with curcumin. The patients underwent autonomic (COMPASS-31), motor (MDS-UPDRS and H&Y) and nonmotor (NMSS) questionnaires and skin biopsies to evaluate clinical involvement and p-syn load in skin nerves at the beginning and the end of study. Curcumin and curcuminoid levels were assayed in plasma and CSF. Supplemented patients showed detectable CSF curcuminoid levels that were lower than those in plasma. They showed a decrease of COMPASS-31 and NMSS scores, and a slight p-syn load decrease versus untreated patients who displayed a worsening of these parameters despite increased levodopa doses. Multiple regression models showed a significant effect of curcumin supplementation in decreasing the worsening of the clinical parameters and p-syn load at after curcumin treatment. These data suggest that curcumin can cross the blood-brain barrier, that it is effective in ameliorating clinical parameters and that it shows a tendency to decrease skin p-syn accumulation in PD patients.